2015
DOI: 10.1001/jamapediatrics.2015.74
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adverse Pregnancy Outcomes With Glyburide vs Insulin in Women With Gestational Diabetes

Abstract: IMPORTANCE Glyburide is thought to be safe for use during pregnancy for treatment of gestational diabetes mellitus (GDM). However, there are limited data on the effectiveness of glyburide when compared with insulin as used in a real-world setting.OBJECTIVE To estimate the risk of adverse maternal and neonatal outcomes in women with GDM treated with glyburide compared with insulin. DESIGN, SETTING, AND PARTICIPANTSRetrospective cohort study of a population-based cohort from a nationwide US employer-based insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 26 publications
1
50
2
5
Order By: Relevance
“…Where possible, we linked mothers to offspring by identifying newborns within the same insurance plan family grouping with birth coding (ICD-9-CM codes V30-V37) within 7 days of the mother’s delivery code to account for slight differences in billing and enrollment timing between the mother and child[14, 20, 21]; linkage was not possible if the mothers and newborns were covered by different insurance plans. We estimated gestational age at delivery by imputing standard ages based on delivery prematurity or post-term delivery diagnoses codes from the mother and linked child.…”
Section: Methodsmentioning
confidence: 99%
“…Where possible, we linked mothers to offspring by identifying newborns within the same insurance plan family grouping with birth coding (ICD-9-CM codes V30-V37) within 7 days of the mother’s delivery code to account for slight differences in billing and enrollment timing between the mother and child[14, 20, 21]; linkage was not possible if the mothers and newborns were covered by different insurance plans. We estimated gestational age at delivery by imputing standard ages based on delivery prematurity or post-term delivery diagnoses codes from the mother and linked child.…”
Section: Methodsmentioning
confidence: 99%
“…Glyburide was associated with higher rates of pre-eclampsia and need for phototherapy in infants, but fewer infants from the glyburide group were admitted to NICU 77. In contrast, a retrospective cohort study comparing outcomes in 4982 women treated with glyburide and 4191 women treated with insulin found that glyburide treatment was associated with increased risk of NICU admission, respiratory distress, hypoglycemia, birth injury, and LGA birth weight 78. This study was limited by the lack of information on glycemic control or maternal body mass index.…”
Section: Glyburidementioning
confidence: 96%
“…An additional study in 2073 women also found higher odds of neonatal intensive care admission (adjusted odds ratio 1.46, 95%CI 1.07–2.00) and birth weight >4000 g (adjusted odds ratio 1.29, 95% CI 1.03–1.64) amongst infants born to mothers receiving glibenclamide during pregnancy 27. The evidence now indicates that glibenclamide treatment in the third trimester exacerbates fetal hyperinsulinism in utero and has an additive effect on birth weight 10, 26, 28. These studies have raised concern regarding the use of glibenclamide in pregnancy 25.…”
Section: Sulfonylurea Treatment In Pregnancy In Type 2 Diabetes and Gmentioning
confidence: 99%
“…More recent publications have demonstrated an increased risk of obstetric and neonatal complications with sulfonylurea use. Even though good glycaemic control may be maintained, pregnant women with GDM treated with glibenclamide had larger babies than insulin‐treated mothers, further increasing the risk of obstetric and neonatal complications from macrosomia 25, 26. In a meta‐analysis of randomized controlled trials, glibenclamide use resulted in greater birth weight (mean difference 109 g; 95% CI 36–181), and higher risks of macrosomia [risk ratio (RR) 2.62, 95% CI 1.35–5.08) and fetal hypoglycaemia (RR 2.04, 95% CI 1.30–3.20) 10.…”
Section: Sulfonylurea Treatment In Pregnancy In Type 2 Diabetes and Gmentioning
confidence: 99%
See 1 more Smart Citation